Japan’s Role in Conflict Resolution and Effective Governance in Tajikistan: Case of the Tajik civil war, 1992-1997 - Usmonov, Farrukh (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
Tajikistan faced Civil War in 1992-1997, which damaged country’s economy and infrastructure. Thus from 1994 Government and United Opposition with support of International society started Inter-Tajik negotiation process, which ended up with signing Peace Treaty in 1997. Japan unlike other countries of the region wasn’t much involved into conflict in Tajikistan, but in opposite, it was supportive into the peace enhancement in country. In 1999 Japanese government created platform for the Inter-Tajik Peace negotiators (including officials from government and opposition of Tajikistan, UN envoys, representatives from IOs and NGOs, Japanese MoFA and other experts) and invited them to Japan to discuss outcome of the Peace Treaty and to look forward on solving remaining issues before Parliamentary election in year 2000. This project considered as final international dialogue between Tajikistani side and International society before country moves onward. Current paper focuses on topic which was discussed in Tokyo, and define outcome of this project.